Peer Mediated Intervention for Improving Social Skills of Children with Learning Disabilities in Inclusive Elementary School - Marlina Marlina (Jurnal Pendidikan Humaniora, 2014)
Peer Mediated Intervention untuk Meningkatkan Keterampilan Sosial Anak Berkesulitan Belajar di Sekolah Dasar InklusifAbstract: This study aims to test the effectiveness of peer mediated intervention (PMI) to improve social skills at children with learning disabilities in SDN 03 Alai Padang. This study used a single subject design with multiple baseline across subject models. Five children with mild learning disabilities as a target child and five trained peer mediator to apply PMI in the lessons Indonesian (repeated reading). Data collected with the recording frequency of social skills format, social skills scale, and self-report. The results showed that PMI was effective for improving the social skills for the targeted children respectively are: the TS’s; the KY’s; the HL’s; the RA’s; and the KA’s. As the instructional effects, PMI also decreased the frequency of reading mistakes at the targeted children from baseline phase to intervention phase. Based on the research findings, it is suggested towards the teachers to apply PMI in other subjects while coordinating with the special teachers. The research findings also provide a theoretical contribution to the social skills learning strategies with peer involvement on the children with learning disabilities in the inclusive elementary school.Key Words: peer mediated intervention, social skills, children with specific learning disabilities Abstrak: Penelitian ini bertujuan menguji efektivitas peer mediated intervention (PMI) untuk meningkatkan keterampilan sosial pada anak berkesulitan belajar di SDN 03 Alai Padang. Penelitian menggunakan single subject design dengan model multiple baseline across subject. Lima anak berkesulitan belajar ringan sebagai anak target dan lima peer mediator dipilih dan dilatih untuk menerapkan PMI dalam pelajaran bahasa Indonesia (membaca ulang). Data dikumpulkan dengan format pencatatan frekuensi keterampilan sosial, skala keterampilan sosial, dan self report. Hasil penelitian menunjukkan PMI efektif meningkatkan keterampilan sosial, yaitu pada anak target TS, KY, HL, RA, dan KA. Sebagai instructional effects, PMI juga efektif mengurangi frekuensi kesalahan membaca anak target pada fase baseline menurun selama intervensi. Disarankan guru menerapkan PMI dalam mata pelajaran lain dan berkoordinasi dengan guru pembimbing khusus. Temuan penelitian memberikan sumbangan teoritik tentang strategi pembelajaran keterampilan sosial yang melibatkan teman sebaya pada anak berkesulitan belajar di sekolah dasar inklusif.Kata kunci: peer mediated intervention, keterampilan sosial, anak berkesulitan belajar